Phenotypical, Clinical, and Molecular Aspects of Adults and Children With Homozygous Familial Hypercholesterolemia in Iberoamerica - Alves, Ana Catarina (2020)
Objective: Characterize homozygous familial hypercholesterolemia (HoFH) individuals from Iberoamerica. Approach and Results: In a cross-sectional retrospective evaluation 134 individuals with a HoFH phenotype, 71 adults (age 39.3±15.8 years, 38.0% males), and 63 children (age 8.8±4.0 years, 50.8% males) were studied. Genetic characterization was available in 129 (96%). The majority (91%) were true homozygotes (true HoFH, n=79, 43.0% children, 46.8% males) or compound heterozygotes (compound heterozygous familial hypercholesterolemia, n=39, 51.3% children, 46.2% males) with putative pathogenic variants in the LDLR. True HoFH due to LDLR variants had higher total (P=0.015) and LDL (low-density lipoprotein)-cholesterol (P=0.008) compared with compound heterozygous familial hypercholesterolemia. Children with true HoFH (n=34) tended to be diagnosed earlier (P=0.051) and had a greater frequency of xanthomas (P=0.016) than those with compound heterozygous familial hypercholesterolemia (n=20). Previous major cardiovascular events were present in 25 (48%) of 52 children (missing information in 2 cases), and in 43 (67%) of 64 adults with LDLR variants. Children who are true HoFH had higher frequency of major cardiovascular events (P=0.02), coronary heart (P=0.013), and aortic/supra-aortic valve diseases (P=0.022) than compound heterozygous familial hypercholesterolemia. In adults, no differences were observed in major cardiovascular events according to type of LDLR variant. From 118 subjects with LDLR variants, 76 (64%) had 2 likely pathogenic or pathogenic variants. In 89 subjects with 2 LDLR variants, those with at least one null allele were younger (P=0.003) and had a greater frequency of major cardiovascular events (P=0.038) occurring at an earlier age (P=0.001). Conclusions: There was a high frequency of cardiovascular disease even in children. Phenotype and cardiovascular complications were heterogeneous and associated with the type of molecular defect.